Design Of Competitiveness Index Software of Food Small Medium Industries (SMI) With Diamond Porter Model Adaptation - Ryan Ardianto; Roni Kastaman; Irfan Ardiansah; Totok Pujianto (Journal of Industrial and Information Technology in Agriculture, 2017)
Small Medium Enterprises (SME) in food was contributed 13,15% on Gross Domestic Product (GDP) 2013. However, SMEs in food had the problems in the management organization that could affect the product competitiveness. The local SMEs in food is less competitive compared with the similar foreign overseas product. In order to anticipate the negative impact of the broader market, the competitiveness measurement was needed to be conducted on understanding the strength of SMEs in food. Competitive measurement can be done by creating web application to reduce measuring process. This research using Designing methods (system engineering) using diamond porter model as competitiveness measurement method of SME in foods. Web application functioned as SME in foods grading, competitiveness weighing, SME in foods index measurements and City SMEs index measurements. Index value that were yielded grouped into three categories which were high, medium, and low. There was a color indicator on index value display that functioned to classifying competitiveness index value. ID was needed to access this web application, those things intended to guard the safety of data contained in this web application.